Discovery of potent and orally bioavailable indazole-based glucagon receptor antagonists for the treatment of type 2 diabetes. Issue 20 (15th October 2019) - Xu, Guozhang; Gaul, Michael D.; Song, Fengbin; Du, Fuyong; Liang, Yin; DesJarlais, Renee L.; DiLoreto, Karen; Shook, Brian; Rentzeperis, Dennis; Santulli, Rosie; Eckardt, Annette; Demarest, Keith
Graphical abstract: Highlights: A new series of indazole-based glucagon receptor antagonists were disclosed. An enantioselective synthesis of indazole derivatives was developed. Lead compound 13K showed robust in vivo efficacy in an acute dog glucagon challenge test. Abstract: Type 2 diabetes mellitus (T2DM) is characterized by chronically elevated plasma glucose levels. The inhibition of glucagon-induced hepatic glucose output via antagonism of the glucagon receptor (GCGR) using a small-molecule antagonist is a promising mechanism for improving glycemic control in the diabetic state. The present work discloses the discovery of indazole-based β-alanine derivatives as potent GCGR antagonists through an efficient enantioselective synthesis and structure-activity relationship (SAR) exploration and optimization. Compounds within this class exhibited excellent pharmacokinetic properties in multiple preclinical species. In an acute dog glucagon challenge test, compound 13K significantly inhibited glucagon-mediated blood glucose increase when dosed orally at 10 mg/kg.